Ambient air quality monitoring : a comparison between two urban parks in Soweto, South Africa - Valsamakis, Sophia Katerina (My University, 2016)
Soweto is identified as an air pollution hot spot area which is characteristic of poor air quality where ambient air pollutant concentrations frequently exceed the South African Ambient Air Quality Standards. Urban greening programmes are seen as a way for cities to work towards reducing air pollution, offsetting greenhouse gas emissions and improve ambient air quality. The City of Johannesburg embarked on the Greening Soweto project in 2006 where many degraded open spaces were transformed into urban green parks and 6000 trees were planted. The urban parks and trees are believed to serve several environmental benefits; one of which includes the improvement in local ambient air quality. The aim of this research was to assess and compare the local ambient air quality situation at two different urban park types in close proximity, Thokoza Park (older trees) and Petrus Molefe Eco-Park (young trees), in Soweto and establish whether the air pollutants measured at the urban parks were lower compared to the urban background conditions. Furthermore, this study assessed whether the ambient concentrations of the selected criteria air pollutants were within the South African National Ambient Air Quality Standards. Three ambient air quality monitoring campaigns were conducted during the spring (October) and winter (June and July) seasons of 2013 and 2014 with the use of a mobile air quality monitoring station. The findings of this research suggest that urban trees in Thokoza Park and Petrus Molefe Eco-Park has the greatest potential to improve air quality in Soweto mainly through changes in local meteorological conditions, specifically for temperature and wind fields, rather than direct removal of air pollutants. Differences in the concentrations of the air pollutants at the different sites showed a strong relationship with changes in temperature, wind speed and direction and emission source types. A significant difference in air pollutant concentrations between the two urban park types was only found for particulate matter (PM10 and PM2.5) and CO2. In general, lower air pollutant concentrations were recorded at the urban parks compared to the urban background site, particularly during the spring season. This study also suggests that the urban trees could represent a potential O3 sink during the spring and winter seasons and for NOx during the spring season. Exceedances of the South African Ambient Air Quality Standards at the two urban parks were only observed for PM10 and PM2.5 during the winter season of 2014. PM10 and PM2.5 and NOx were identified to be air pollutants of concern at the urban parks in comparison to other criteria air pollutants assessed in this study. Maximum daily concentrations of 255 μg/m3 for PM10 and 126 μg/m3 for PM2.5 and a maximum hourly concentration of 92 ppb for NOx were recorded at the parks during winter season
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. 14 August 2015
Keywords: Air--Pollution.; Environmental control.; Urban parks--South Africa--Soweto.